2013
DOI: 10.1007/s12031-013-0059-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association Analysis of ITGB3 Polymorphisms with Age at Onset of Schizophrenia

Abstract: Schizophrenia (SCZ) is a debilitating disorder with a prevalence of approximately 1 % worldwide. SCZ is known to have a high degree of genetic and clinical heterogeneity and is a major health problem worldwide. The integrin-β 3 subunit gene (ITGB3) gene at 17q21.32 has been implicated in psychiatric disorders. We therefore hypothesized that ITGB3 gene polymorphisms might also play a role in SCZ and age at onset (AAO) of SCZ. We investigated the genetic associations of 23 single-nucleotide polymorphisms (SNPs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Indeed, mice lacking Itgb3 exhibit behavioural abnormalities with a strong analogy to ASD in humans, including abnormal social interactions and repetitive behaviour (Carter et al, 2011). ITGB3 gene variants in humans are also linked to the age of onset in schizophrenia (Wang et al, 2013). Mechanistically, β3 integrin expression regulates the brain serotonin (5-HT) system, a key neurotransmitter pathway.…”
Section: Box 2 Integrin Ligands In the Cnsmentioning
confidence: 99%
“…Indeed, mice lacking Itgb3 exhibit behavioural abnormalities with a strong analogy to ASD in humans, including abnormal social interactions and repetitive behaviour (Carter et al, 2011). ITGB3 gene variants in humans are also linked to the age of onset in schizophrenia (Wang et al, 2013). Mechanistically, β3 integrin expression regulates the brain serotonin (5-HT) system, a key neurotransmitter pathway.…”
Section: Box 2 Integrin Ligands In the Cnsmentioning
confidence: 99%
“…Integrins, a family of heterodimeric cell adhesion molecules (CAMs) consisting of several different α - and β -subunits, interact with ECM molecules to carry out a multitude of developmental and adult brain functions. Support for the idea that integrins may be implicated in the pathology of schizophrenia comes in part from genetic studies pointing to association of this disorder with a number of integrin gene variants, such as SNPs in the ITGA8 and ITGB3 genes [ 81 , 82 ]. Additional evidence supporting the involvement of integrins in schizophrenia includes increased expression of integrin α (IIb) and β (IIIa) in first episode subjects with schizophrenia and, notably, abnormal cell adhesion in cultures from olfactory mucosa biopsies from patients with this disorder, which was ameliorated by antibodies blocking integrins [ 83 , 84 ].…”
Section: Schizophreniamentioning
confidence: 99%
“…For example, altered expression of ITGA8 and ITGB3 have been observed in Sz [61, 62]. In addition, a flow cytometry study analyzed surface expression of several glycoproteins and found a significant increase in integrin α2 b β3 a expression in first episode Sz patients compared with healthy controls [63].…”
Section: Changes In Brain Ecm In Neurodegenerative Conditionsmentioning
confidence: 99%